Perbanyakan In Vitro Bawang Putih (Allium Sativum Var. Tawangmangu) Melalui Kultur Tunas Kapital (Shoot Apex) - Dian Latifa; Tia Setiawati; Ruly Budiono (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
The purpose of this research was to get the best combination of NAA and BAP concentration that enhance the growth of shoots and the best IBA concentration to root inducing from shoot apex explants of garlic on semi-solid MS medium. Research used experimental method with single factor and 2 steps induction of research, those are shooting and rooting. For the steps of shoot induction, the treatment used 9 combinations concentration BAP and NAA (k), those were k1 (NAA 0,25 ppm + BAP 1 ppm), k2 (NAA 0,5 ppm + BAP 1 ppm), k3 (NAA 0,75 ppm + BAP 1 ppm), k4 (NAA 0,25 ppm + BAP 1,5 ppm), k5 (NAA 0,5 ppm + BAP 1,5 ppm), k6 (NAA 0,75 ppm + BAP 1,5 ppm), k7 (NAA 0,25 ppm + BAP 2 ppm), k8 (NAA 0,5 ppm + BAP 2 ppm) and k9 (NAA 0,75 ppm + BAP 2 ppm). While for root induction used 3 treatments, those were i1 (IBA 1 ppm), i2 (IBA 2 ppm) dan i3 (IBA 3 ppm). The fastest time of shoot’s growth was 4,66 days after planting that appeared on k7 treatment. The treatment of k4 was the best average of the number shoots and leaves (2,66 and 4). Treatment of k3 was the best average of the lenght shoots and leaves (7,33 and 8,03). In the step of root induction, i2 is fastest time for root inductions (10 day after root induction) and the best average of the number root (2,66). Furthermore, i1 treatment was the best average of the lenght root (0,47 cm).Keywords: Garlic, MS, Plant growth regulator, Shoot apex, Tissue culture